Technology versus Design Innovation's Effects on Sales and Tobin's Q: The Moderating Role of Branding Strategy. Issue 3 (2nd April 2013) - Rubera, Gaia; Droge, Cornelia
<x xml:space="preserve">Abstract</x> This research investigates the impacts on firm performance of (1) technology versus design innovation and (2) their potentially synergistic interaction. Synergies could arise from complementarities, in particular the utilization of technology innovation as a platform for design innovations. Both sales and Tobin's q are examined as dependent performance variables, with sales tapping consumer responses and Tobin's q reflecting investor responses. Moderation by branding strategy (i.e., Corporate Branding versus Mixed Branding versus House of Brands) is analyzed because innovation may impact performance differently depending on branding strategy. Advertising effects, the number of new product introductions, their interaction, R&D expenditures, operating margins, and firm size are also modeled as covariates. The results show that all main and interaction effects are significant in at least one of the branding groups, and that moderation of model paths by branding strategy was pervasive. Overall, except for technology innovation → Tobin's q, Corporate Branding coefficients for technology innovation, design innovation, and their interaction were almost always significantly different from Mixed Branding and House of Brands coefficients, which were not significantly different from each other. Since Mixed Branding and House of Brands proved very similar, these groups were combined under "Non‐Corporate." First, for technology innovation, the impact on both sales and Tobin's q for Corporate Branding was less than or equal to Noncorporate. Noteworthy was that the technology innovation → Tobin's q relationship was equal across all branding strategies; technology innovation appears to be key for investors. Second, for design innovation, the impact for Corporate Branding was positive while for Noncorporate it was null; the same pattern was observed for sales and Tobin's q. Third, for the interaction, the impact for Corporate Branding was significantly less than the positive impacts for Noncorporate. For Noncorporate, the marginal impact of design innovation on sales or Tobin's q increased with the level of technology innovation. For Corporate Branding however, there was no interaction in the case of sales and a negative interaction for Tobin's q. Thus, the marginal impact of design innovation on Tobin's q decreased with increasing levels of technology innovation. These decreasing marginal effects could reflect limits to corporate brand name extensions, as perceived by investors.